Pengaruh Pendidikan Kewirausahaan, Motivasi Berprestasi, dan Lingkungan Sosial terhadap Intensi Berwirausaha Mahasiswa FKIP UNS Angkatan 2019 - Eka Nur Hidayati; Trisno Martono; Sudarno Sudarno (Departement of Mathematics Education, 2024)
The purpose of this study was to determine 1) the effect of entrepreneurship education on entrepreneurial intention of FKIP UNS students class of 2019; 2) the effect of achievement motivation on entrepreneurial intention of FKIP UNS students class of 2019; 3) the effect of social environment on entrepreneurial intention of FKIP UNS students class of 2019; 4) the effect of entrepreneurship education, achievement motivation, and social environment on entrepreneurial intention of FKIP UNS students class of 2019. This research is a quantitative study with a population of the FKIP UNS class of 2019. The sampling technique used Proportionate Random Sampling with a sample size of 322 respondents. Data collection techniques using questionnaires and data analysis using multiple linear regression analysis. The results showed that 1) there is a positive and significant effect of entrepreneurship education on entrepreneurial intention of FKIP UNS students class of 2019; 2) there is a positive and significant effect of achievement motivation on entrepreneurial intention of FKIP UNS students class of 2019; 3) there is a positive and significant effect of social environment on entrepreneurial intention of FKIP UNS students class of 2019; 4) there is a positive and significant effect of entrepreneurship education, achievement motivation, and social environment on entrepreneurial intention of FKIP UNS students class of 2019.